"Big Luther" discourse: cultural longing and the signification of Luther Vandross in African American popular culture. Issue 2 (4th May 2023) - Moore, Marlon Rachquel
ABSTRACT: With a catalog that stretches from the 1960s into the early 2000s, Luther Vandross is highly esteemed internationally and across multiple generations of music fans. For many, he is essential to the soundtrack of their emotional lives. His stylings are such a large part of the Black cultural imaginary in the United States that, since the 1980s, Vandross has been figured in literature, film, Hip Hop lyrics, and television shows to convey romantic sentiments or a seductive mood in heterosexual and queer contexts. But in some cases, he is admonished and fat shamed, and held up as a symbol of the ways in which "good health" eludes the African American community statistically. I want to linger in that ambivalence and highlight the various shades of meaning that have been attached to Vandross' fat (and sometimes slim) body in narratives produced for mass culture and smaller targeted audiences. To that end, I take up "Big Luther" discourse as an analytical framework to examine artistic and communal articulations that weaponize "care" and "concern" for Vandross, including the 1996 film The Nutty Professor, a 2006 episode of the animated sitcom The Boondocks, and Divabetic, a diabetes awareness organization that his mother was involved in establishing after Vandross died in 2005.